UPAYA PENINGKATAN BUDAYA K3 (KESELAMATAN DAN KESEHATAN KERJA) PADA UKM BENGKEL LAS PINTU HARMONIKA “JAYA MANDIRI” DENGAN PENGGUNAAN ALAT PELINDUNG DIRI - I Wayan Joniarta; Anak Agung Alit Triadi; Arif Mulyanto; I Dewa Ketut Okariawan; Paryanto Dwi Setyawan (Universitas Mataram, 2022)
Counseling and socialization of the use of Personal Protective Equipment (PPE) is one of the efforts to support Occupational Health and Safety. Welding workshop